The Application of Foot Exercise Increases Ankle Brachial Values Index (ABI) in Type 2 Diabetes Mellitus Patients at Fatmawati General Hospital: Case Report: Senam Kaki sebagai upaya peningkatan Ankle Brachial Index (ABI) Pada Pasien Diabetes Melitus Tipe 2: Laporan Kasus - Jatmiko, Salsabilla Aulia; Tarwoto, Tarwoto (Essential English Grammar, 2024)
Diabetes Mellitus is a chronic disease characterized by blood glucose (blood sugar) levels exceeding normal. Long-term complications of type 2 diabetes mellitus can include microangiopathy and macroangiopathy. Microvascular complications include neuropathy, while macrovascular damage includes damage to the peripheral blood vessels of the legs, which is usually called diabetic foot. Diabetic foot exercises, including physical exercise, are natural exercises that are practical in increasing perfusion to the periphery or can increase the Ankle Brachial Index (ABI) value in patients with type 2 diabetes mellitus, especially in the foot area. This study aimed to analyze the application of foot exercise interventions in patients with Type 2 Diabetes Mellitus to increase peripheral perfusion in the foot area. This research method uses a case report method with interventions carried out on one patient for  15-30 minutes per day for 3 days. The evaluation results after the foot exercise intervention found a change in the ABI value for the right leg from 0.91 to 1.04 and the left leg from 0.90 to 0.97. This shows that after the foot exercise intervention, the Ankle Brachial Index (ABI) value increased. It is hoped that foot exercises for Diabetes Mellitus patients can be applied to patients while in hospital and can continue to be practiced independently by patients while at home